2007
DOI: 10.1021/jp074789c
|View full text |Cite
|
Sign up to set email alerts
|

Side-by-side ZnSe/ZnCdSe Bicrystalline Nanoribbons Prepared by a Two-Step Process

Abstract: By a two-step method, side-by-side bicrystalline ZnSe/ZnCdSe nanoribbons were fabricated via metalorganic chemical vapor deposition. The nanoribbons were characterized by secondary and transmission electron microscopy, and energy dispersed X-ray spectroscopy. A good epitaxial relationship and a sharp interface exist between the two crystals, despite their different crystalline orientation and composition. The lattice mismatch induced strain is fully accommodated by bending. Two mechanisms, the vapor−liquid−sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Wang et al showed the growth of ZnO/ZnSe core/shell NW arrays on transparent conducting oxide substrates, which had potential applications in solar cells [70]. The formation of side-byside ZnSe/ZnCdSe bicrystalline NRs was accomplished by a two-step process employing MOCVD [71], and ZnSe/Si bicoaxial NWs were formed by one-step thermal evaporation [72]. Interestingly, it was found that CdSe quantum dots in ZnSe could function as efficient source for single photons [73].…”
Section: Znsementioning
confidence: 99%
“…Wang et al showed the growth of ZnO/ZnSe core/shell NW arrays on transparent conducting oxide substrates, which had potential applications in solar cells [70]. The formation of side-byside ZnSe/ZnCdSe bicrystalline NRs was accomplished by a two-step process employing MOCVD [71], and ZnSe/Si bicoaxial NWs were formed by one-step thermal evaporation [72]. Interestingly, it was found that CdSe quantum dots in ZnSe could function as efficient source for single photons [73].…”
Section: Znsementioning
confidence: 99%
“…7 In contrast to the one-stage syntheses, two-stage fabrications are generally accompanied by variations (i.e., compositions, temperature, and reaction pressure) and thus offer more flexibility in combining different materials and allow separate controls over each material in the single stage. Novel {113} twinned ZnSe bicrystal nanobelts filled with 〈111〉 twinnings 11 and side-by-side ZnSe/ZnCdSe bicrystalline nanoribbons 12 have been successfully synthesized through this method. However, reports on the two-stage fabrication of one-dimensional (1D) nanostructures are relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches have been developed to fabricate the nanowire and the silica sheath in one step; ,,, although maybe simple, they could not easily control the dimension of the nanowires and the silica sheath independently. Hence, a two-step method is instructive for the synthesis of the heterostructure. , Some chemical methods have been generated to fabricate nanocables at relatively low temperature, but they are not suitable for the applications like direct integration of FETs. Furthermore, a general method is still absent to controllably coat silica sheath on series of 1D nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a two-step method is instructive for the synthesis of the heterostructure. 7,19 Some chemical methods have been generated to fabricate nanocables at relatively low temperature, [20][21][22] but they are not suitable for the applications like direct integration of FETs. Furthermore, a general method is still absent to controllably coat silica sheath on series of 1D nanomaterials.…”
Section: Introductionmentioning
confidence: 99%